The Effect of Audit Fee, Audit Opinion, and KAP Size on Audit Delay - Syawalica Fifah Nurcahya; Sugeng Sugeng (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Financial statements are the company's primary means of communication with stakeholders. External audits ensure the fairness of financial statements in accordance with accounting standards. However, delays in submitting financial statements (audit delay) are still a phenomenon in Indonesia, especially in the financial sector. This study aims to determine the effect of audit fees, audit opinions, and KAP size on audit delays in financial sector companies listed on the Indonesia Stock Exchange in 2019 - 2023. The data used in this study are secondary data obtained from financial statements and annual reports of financial sector companies listed on the Indonesia Stock Exchange in 2019 - 2023. The sampling technique in this study is the purposive sampling method according to predetermined criteria with a population of 104 companies during 2019 - 2023, and obtaining a final sample of 193. The analysis method used is multiple linear regression to test the relationship between independent variables, namely audit fees, audit opinions, and KAP size, to the dependent variable, namely audit delay, using the Statistical program for Social Science (SPSS) version 24. The results of the study indicate that audit fees have a significant negative effect on audit delay. High audit fees allow auditors to provide sufficient resources to complete the audit process on time. Audit opinions also have a negative effect on audit delay. Companies that receive an unqualified opinion tend to complete audit reports faster than companies that receive other opinions. KAP size has a negative effect on audit delay, where Big Four KAPs complete audits faster than non-Big Four KAPs.